2019
DOI: 10.3390/jcm8091273
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Effects on Extra-Osseous Subtalar Arthroereisis

Abstract: Implant extrusion in subtalar arthroereisis is a common complication for pediatric flexible flatfoot. However, there were a limited number of articles addressing the body weight effects on implant extrusion after the procedure. We conducted a 24-month follow-up assessment after subtalar arthroereisis. Surgical patients who underwent the Vulpius procedure were retrospectively collected from May 2010 to January 2017, including 59 cases of both feet having implants in situ and 43 cases of both feet having implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Bioabsorbable material may be associated with regional inflammatory response 1,30 . Higher body mass index was found to be associate with higher complication rates and less deformity correction with endosinotarsal implants 21 . Careful selection of patients and techniques based on current evidence may be helpful to reduce the complication rate.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bioabsorbable material may be associated with regional inflammatory response 1,30 . Higher body mass index was found to be associate with higher complication rates and less deformity correction with endosinotarsal implants 21 . Careful selection of patients and techniques based on current evidence may be helpful to reduce the complication rate.…”
Section: Discussionmentioning
confidence: 89%
“…In terms of the patient population, 6 studies performed with endosinotarsal cone shaped implant [20][21][22][23] , 5 studies performed with exosinotarsal screw [24][25][26][27][28][29] , while one study performed with both surgeries were divided into two groups 1 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, considering the bone fragility of OI patients, the migration or even extrusion of the implant resulting in erosion of bone surfaces adjacent to the implants was once the major concern in our series. The reported complication rate due to implant extrusion ranges between 0.5% and 9% across all implant types [ 10 ], where pediatric patients with a higher BMI need to be handled cautiously due to their higher implant extrusion rate and worse outcomes [ 17 ]. However, the postoperative and follow-up weight-bearing radiographs showed that adjacent bony surfaces to implants remained intact, which could be attributed to less osteochondral damage of SA and the reduced mobility of OI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is initial evidence that lateral arthroereisis may offer a potentially less-invasive alternative to lateral column lengthening [71]. On the other hand, potential disadvantages and complications of the subtalar arthroereisis include loosening, breakage of the implant, pain and discomfort at the surgical incision, peroneal spasm, joint effusion, stress fracture and infection [69,70,72,73]. Although there is no evidence about the role of the hardware removal, in our practice we routinely remove the calcaneo-stop screw 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%